A potential role of a substrate as a base for the deprotonation pathway in Rh-catalysed C–H amination of heteroarenes: DFT insights. Issue 19 (12th April 2016) - Ajitha, Manjaly J.; Huang, Kuo-Wei; Kwak, Jaesung; Kim, Hyun Jin; Chang, Sukbok; Jung, Yousung
Abstract : DFT studies suggest that basic substrates assist the C–H activation step in Rh-catalysed reactions and transport protons towards the protodemetallation step. Abstract : The possibility of direct introduction of a new functionality through C–H bond activation is an attractive strategy in covalent synthesis. Here, we investigated the mechanism of Rh-catalysed C–H amination of the heteroaryl substrate (2-phenylpyridine) using phenyl azide as a nitrogen source by density functional theory (DFT). For the deprotocyclometallation and protodecyclometallation processes of the title reaction, we propose a stepwise base-assisted mechanism (pathway I) instead of the previously reported concerted mechanism (pathway II). In the new mechanism proposed here, 2-phenylpyridine acts as a base in the initial deprotonation step (C–H bond cleavage) and transports the proton towards the final protonation step. In fact, the N–H bond of the strong conjugate acid (formed during the initial C–H bond cleavage) considered in pathway I ( via TS4 ) is more acidic than the C–H bond of the neutral substrate considered in pathway II ( via TS5 ). The higher activation barrier ofTS5 mainly originates from the ring strain of the four-membered cyclic transition state. The vital role of the base, as disclosed here, can potentially have broader mechanistic implications for the development of reaction conditions of transition metal-catalysed reactions.